Haemoglobin Level in Children of a Northern District of Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Objective: To find out the reference level of haemoglobin and other haematological parameters(PCV, MCV, MCH, MCHC, S. Iron and S. Ferritin) of the children of Northern area of Bangladesh and to see the relation of socio demographic features and other haematological parameters with haemoglobin level.Methodology: Observational cross sectional study.Setting: Outpatient department of Rangpur Medical College and outpatient department of eight Upozilla Health Complexes of northern Bangladesh.Patients: 300 clinically healthy 1yr. to 14yr. age children.Outcome measures: Mean Hb. level in age groups and influence of sex, age, economic status, parental education, nutrition and serum iron on level of Hb. PCV, MCV, MCH, MCHC, S. Iron and S. Ferritin was estimated to see the confounders and if they are affecting Hb. level significantly.Results: Mean haemoglobin among study population was 11.4gm/dl(SD;1.07). Haemoglobin was normally distributed among the study population. Mean haemoglobin among age groups differed significantly. No significant difference in mean haemoglobin was observed among two sex groups. Mean haemoglibin level corresponded well with WHO defined haemoglobin level in the same age group of children.Conclusion: Reference level of mean Hb. in the studied population is 11.4gm/dl(SD;1.07). Age affects the Hb. level but sex doest. Hb. level in this population is comparable with WHO reference value for this age. DOI: http://dx.doi.org/10.3329/jbcps.v30i3.12460 J Bangladesh Coll Phys Surg 2012; 30: 127-131